Public health updates from October 2019 to April 2020 - Annu Antony; R Akshaya; Jyolsna Nair (Wolters Kluwer Medknow Publications, 2020)
Public health is a very dynamic area, were the policies, guidelines, management is continuously monitored and amended to the current situation. Epidemics and pandemics are now frequent and more widespread due to globalization. In this scenario, being updated in public health related news and changes are must for an effective community medicine practice. Our article concisely presents all the relevant updates from the month of October 2019 to April 2020. This article discusses the timeline of COVID-19 pandemic in this period, Ebola epidemic, new changes in national programs, new amendments in National Policies or Acts, new schemes implemented, and also discusses the yearly themes of international and national days related to public health celebrated during the time frame.